Phospho-mTOR (Ser2481) colocalizes with condensed chromosomes during metaphase - Kosach, V.R.; Tykhonkova, I.O.; Cherednyk, O.V.; Filonenko, V.V.; Khoruzhenko, A.I. (Вiopolymers and Cell, 2016)
Aim. To study the subcellular localization of phospho-mTOR (Ser2481) in cultured cells of human cancer cell lines. Methods. Immunofluorescent analysis of phospho-mTOR (Ser2481) subcellular localization in cultured MCF-7 (human breast adenocarcinoma) and HepG2 (human liver carcinoma) cells. Results. For the first time phospho-mTOR (Ser2481) was detected as bright spots situated in the equatorial region of chromosomes and colocalized with condensed chromosomes during metaphase. Conclusions. In this study, we describe for the first time the co-localization of phospho-mTOR (Ser2481) and chromosomes of the metaphase plate in the MCF-7 and HepG2 cells. Our data support the hypothesis that phospho-mTOR (Ser2481) could act as a CPP (chromosomal passenger protein)-like kinase, which takes part in the regulation of mitosis progression. Мета. Дослідити внутрішньоклітинну локалізацію phospho-mTOR (Ser2481) в лініях ракових клітин людини. Методи. Подвійний імунофлуоресцентний аналіз. Культивовані клітини ліній MCF-7 (аденокарцинома молочної залози людини) і HepG2 (карцинома печінки людини). Результати. Вперше phospho-mTOR (Ser2481) був виявлений у вигляді яскравих точок, які розташовувались в екваторіальній області клітини та співлокалізувались з конденсованими хромосомами під час метафази. Висновки. У цьому дослідженні ми вперше описуємо співлокалізацію phospho-mTOR (Ser2481) і хромосом метафазної пластинки у клітинах ліній MCF-7 і HepG2. Наші дані підкріплюють гіпотезу, що phospho-mTOR (Ser2481) може виступати в якості СРР-кінази і брати участь у регуляції проходження мітозу. Цель. Исследовать внутриклеточную локализацию phospho-mTOR (Ser2481) в раковых клеточных линиях человека. Методы. Двойной иммунофлуоресцентный анализ. Культивированные клетки линий MCF-7 (аденокарцинома молочной железы человека) и HepG2 (карцинома печени человека). Результаты. Впервые phospho-mTOR (Ser2481) был обнаружен в виде ярких точек, которые располагались в экваториальной области клетки и колокализировались с конденсированными хромосомами во время метафазы. Выводы. В этом исследовании мы впервые описываем колокализацию phospho-mTOR (Ser2481) и хромосом метафазной пластинки в клетках линий MCF-7 и HepG2. Наши данные подкрепляют гипотезу, что phospho-mTOR (Ser2481) может выступать в качестве СРР-киназы и участвовать в регуляции прохождения митоза.